The Symbolic Meaning of Kayah Baarak Tradition in Bengkulu Indigenous Wedding - Nisak, Nisbatun; Endrizal, Endrizal (Kirana Publisher (KNPub), 2024)
This research discusses the Kayah Baarak tradition in the traditional marriage process in the Tunggang Village community. This research aims to find out how the kayah baarak procession in the marriage procession and the meaning in the Kayah Baarak tradition in the traditional marriage process of the Tunggang Village community. This research uses qualitative methods and the data collection techniques are observation, interviews, and documentation. The findings in this study are that the Kayah Baarak tradition has several meanings that can be taken in this procession, one of which is social meaning and religious meaning. The participation of the surrounding community in the Kayah Baarak procession, there can be seen how social values are applied in the procession.